Impact of policy measures and behavior on the COVID pandemic in Germany - Jenny Bethäuser (Philipps-University Marburg, School of Business and Economics, 2024)
Critics protest loudly against restrictions imposed by politicians during the COVID-19 pandemic in Germany: Mandatory masks, lockdowns, school and business closures. This paper examines (1) the extent to which these policies have indirectly contributed to limiting the number of COVID-19 cases and deaths by forcing people to practice social distancing, and (2) the extent to which people have adjusted their social distancing behavior on their own based on information about national case and fatality numbers and therefore directly limit the number of COVID-19 cases and deaths. The panel analysis on federal state level in Germany finds that substantial declines in COVID-19 case and death growth rates are attributable to private behavioral response, but policies played an important role as well. A change in policies explains a large fraction of changes in social distancing behavior, why both policies and national information are important determinants of federal COVID-19 cases and deaths. Due to the lack of cross-sectional variation, there is uncertainty about the effect of mask mandate.
Keywords: C33; C55; I12; I18; 330; COVID-19; Coronavirus; Cases; Deaths; Pandemic; Politics; Mask Mandate; Behavior; Causal Inference; Panel Data